2014
DOI: 10.4097/kjae.2014.67.1.43
|View full text |Cite
|
Sign up to set email alerts
|

The use of 3 sugammadex out of 5 reversal of during recovery of rocuronium-induced neuromuscular blockade in a patient with post-tonsillectomy hemorrhage: a case report

Abstract: Post-tonsillectomy hemorrhage (PTH) is the most frequent complication of tonsillectomy, and occasionally results in a lethal outcome. A 21-year-old man (height 180 cm, weight 95 kg) was scheduled for a bilateral tonsillectomy and uvulopalatopharyngoplasty for treatment of obstructive sleep apnea. He required 5 rounds of general anesthesia due to recurrent PTH. The anesthesiologist used sugammadex a total of 3 times to achieve the successful reversal of the deep neuromuscular blockade (NMB) induced by rocuroniu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
(19 reference statements)
0
6
0
Order By: Relevance
“…Jo et al ( 2012 ) found lower P-peak levels during PCV in both supine and prone positions when compared with VCV. Kim et al ( 2014 ) compared the PCV and VCV modes during prone position in high-level spinal cord injury patients and found that P-peak increased after prone positioning in both groups, but this increase was significantly higher in VCV group compared with PCV group. In our study, compliance levels were lower in both groups in prone position when compared with supine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jo et al ( 2012 ) found lower P-peak levels during PCV in both supine and prone positions when compared with VCV. Kim et al ( 2014 ) compared the PCV and VCV modes during prone position in high-level spinal cord injury patients and found that P-peak increased after prone positioning in both groups, but this increase was significantly higher in VCV group compared with PCV group. In our study, compliance levels were lower in both groups in prone position when compared with supine.…”
Section: Discussionmentioning
confidence: 99%
“…Prone position during general anesthesia for special surgical operations may be related with increased airway pressure, decreased pulmonary and thoracic compliance that may be explained by restriction of chest expansion and compression of abdomen (Tanskanen et al 1997 ; Palmon et al 1998 ). The optimum ventilation mode for anesthetized patients in prone position was not described and studies comparing VCV and PCV during prone position are limited (Choi et al 2009 ; Jo et al 2012 ; Kim et al 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, re-establishing muscle paralysis with rocuronium has even been reported to be possible soon after sugammadex has been applied. [20][21][22] Thus, we believe that the enhanced recovery of muscle paralysis after releasing the tourniquet is not clinically relevant, although it was significant in the present study.…”
Section: Discussionmentioning
confidence: 61%
“…Currently, determining the accurate dose and timing of sugammadex with neuromuscular monitoring, and, if an emergency reoperation is needed for patients who were administered sugammadex, determining the accurate dose and timing of rocuronium has become more important as opposed to selecting an anticholinesterase [ 17 , 18 ]. In addition, if neuromuscular blockade is required for reoperation but cannot be achieved with rocuronium and sugammadex, benzylisoquinoliniums (e.g., cisatracurium) or succinylcholine could probably be used [ 6 , 19 , 20 ]. If cisatracurium is used, rocuronium that did not bind to sugammadex and nicotinic acetylcholine receptors that did not bind neuromuscular blockers could induce priming effects, thereby causing an earlier onset of action for cisatracurium [ 21 ].…”
Section: Discussionmentioning
confidence: 99%